Ways to Study and Research Urban, Architectural and Technical Design - Jong, T.M. de (IOS Press, 2014)
How can we develop a scientific basis for architectural, urban and technical design? When can a design be labelled as scientific output, comparable with a scientific report? What are the similarities and dis-similarities between design and empirical research, and between design research, typological research, design study and study by design? Is there a need for a particular methodology for design driven study and research? With these questions in mind, more than forty members of the Faculty of Architecture of the Delft University of Technology have described their ways of study and research. Each chapter shows the objectives, the methodology and its implementation in search for a deeper knowledge of design processes and an optimal quality of the design itself. The authors - among them architects, urban planners, social scientists, lawyers, technicians and information scientists – have widely differing backgrounds. Nevertheless, they share a great deal. The central focus is a better understanding of design processes, design tools and the effects of design interventions on issues such as utility, aesthetics meaning, sustainability and feasibility.